Study on prevalence and factors associated with the behavioural problems amoung year one school children in Municipal Council area of Matale - Ratnayake, R.M.M (My University, 2007)
It was descriptive cross-sectional study. The Sinhala translation of Rutter's teachers questionnaire, which was validated to use in Sri Lanka was used to find out the 1revalence of the behavioral problems among year one school children. Another questionnaire prepared by the investigator was used to collect information from the mothers. lout of 1464 year one school children 280 were selected for the study. Results showed that It he prevalence of behavioral problems was found to be 18 percent.. This was consistent with some other studies done in the world. It showed the magnitude of the problem. It also showed that boys had a higher degree of behavioral problems, than the girls. Educational status of the mothers showed a positive effect in reducing the behavioral status of the mother was not significantly associated with behavioral problems. Mother's availability during the pre school age couldn't be evaluated due to small proportion of mothers found in the sample. Prevalence of 18 percent of behavioral problems showed the magnitude of the problem in the urban area. Female education has helped to reduce the behavioral problems and must be encouraged.